Other-Initiated Repair Strategies in Solving Understanding Problems in EFL Learners Conversations - Madar Aleksius; Ali Saukah (Journal of Education and Learning (EduLearn), 2018)
The aims of this study were to investigate the employment of Other-Initiated Repair Strategies (OIR Strategies) in solving understanding problem in EFL learners’ conversation and to examine the kinds of trouble sources that prompt the employment of OIR Strategies. The participants were nine EFL learners participating in a speaking class in small university in Indonesia. To elicit the learners’ conversations two communicative tasks, Spot the Difference and Desert Island were used. The learners’ conversations during task performance were video-recorded, then, transcribed using the conventions proposed by Markee (2000) and analyzed qualitatively using Conversation Analysis method. The results showed that EFL learners managed to employ eight types of OIR Strategies comprising of 62 instances in total. The strategies are unspecified repair, interrogative repair, partial repeat plus a question word repair, partial repeat repair, understanding check repair, request for repetition, request for definition, and correction repair. Three different types of trouble sources triggered the use of OIR Strategies, namely linguistic-related problem, interactional-related problem, and meaning-related problem. The study demonstrated that by employing different OIR Strategies, even EFL learners with limited proficiency in English managed to take initiatives to overcome the understanding problem in conversations as part of their learning process. Therefore, the EFL teachers need to consider incorporating the teaching of OIR Strategies as part of their speaking class to improve the students’ fluency.